Near-miss in early pregnancy at Chris Hani Baragwanath Academic Hospital - Madiba, Kholofelo Raisibe (My University, 2021)
Introduction: The concept of maternal near-miss is well documented in South Africa and worldwide, however causes of near-miss in early pregnancy (<24 weeks gestation) need further exploration. A near-miss is a woman who had a life-threatening complication due to pregnancy or childbirth up to 42 days after delivery. Objectives: To determine the frequency and severity of maternal near-miss occurring at less than 24 weeks gestation as a consequence of ectopic pregnancies, termination of pregnancies, miscarriages and molar pregnancies at the Chris Hani Baragwanath Academic Hospital. Methods: This was a retrospective audit of near-miss in early pregnancy cases occurring between 1 January 2015 and 31 December 2016. Case records were reviewed and data was collected by the researcher. Results: Thirty-nine cases of near-miss and 1 maternal death from early pregnancy were found over a 2 year period. Of these, 18 women had a near-miss a s a result of ectopic pregnancies (46.1%), 13 from miscarriages (33.3%), 7 as a consequence of termination of pregnancy (18.0%) and one from a molar pregnancy (2.6%). HIV status and antenatal care booking status were amongst the most recognized risk factors. Twenty (51.3%) of the women were HIV positive and 36 (92.3%) of them had not had any antenatal care visits prior to hospital admission. All the women who had a termination of pregnancy had done so illegally and all women with an ectopic pregnancy were found to have already ruptured at the time of presenting to the hospital. Septic shock occurred in 3 (42.9%) of the 7 women with an illegal termination of pregnancy. The majority (60%) of the women required a blood transfusion of ≥ 4 units. Five (13.5%) women had a hysterectomy as a consequence of haemorrhage or sepsis and 19 women (51.4%) required high care or intensive care admission. Patient related avoidable factors included unsafe termination of pregnancy (18.9%) and delay in seeking medical attention in 27% of the cases. Conclusion: Ectopic pregnancies and unsafe termination of pregnancies were the most frequent causes of near-miss in early pregnancy resulting in severe haemorrhage and sepsis. This suggests that early ultrasound to diagnose ectopic pregnancy, access to contraception to prevent unwanted pregnancies and access to safe TOP services can prevent severe morbidity and mortality. Improving access to antenatal care services, coupled with patient education can improve maternal outcomes in women early in pregnancy
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine, 2021